From mitochondria to cells to humans: Targeting bioenergetics in aging and disease. (April 2023) - Berry, Brandon J.; Pharaoh, Gavin A.; Marcinek, David J.
Abstract: In vivo control over metabolism is at the cutting edge of biomedical research. The particulars of mitochondrial function are especially important to understand in vivo to progress metabolic therapies that will be relevant for diseases of aging. Understanding the differences between how mitochondria function in vitro versus in vivo will be a necessary challenge to overcome to achieve mitochondrial medicine. In this article we outline how discoveries in invertebrate models will be informative for understanding the basic biology of mitochondria to streamline translation to mammals and eventually to humans. Further, we highlight examples of how what is known about mitochondria in vitro is translatable to in vivo models and, in some cases, to human diseases. Highlights: Mitochondria are complex metabolic hubs that are not fully understood. Mitochondria in cells, invertebrates, and tissue are important contexts to study. Achieving mitochondrial medicine will require better understanding in vivo.